The Conservation of the Mosaic Floor of Swaifieh Church, Amman, Jordan - Arinat, Mahmoud (Dirasat: Human and Social Sciences, 2019)
This paper aims to describe the conservation of the mosaic floor of the Swaifieh church in Jordan, which is one of the few remaining byzantine mosaics in Amman region. The mosaic was discovered in 1970. Since then the mosaic floor has been exposed to the different deterioration forms such as lacunae, incrustation, depressions, swelling, detachment between preparatory layers, salt efflorescence, and biological activity. The study confirms that it is necessary to conserve the mosaic floor in order to avoid further damage. The conservation activities carried out on the mosaic floor included documenting the mosaic by photographs and drawings, replacement the cement from lacunae and filling lime mortar, consolidating the mosaic edges and the preparatory layers with lime mortar, mechanical cleaning and replacement of the old shelter plates with new one to avoid rainwater from reaching inside the building.